PELAKSANAAN TUGAS SOUS CHEF PADA FOOD AND BEVARAGE PRODUCT DI LABERSA TOBA HOTEL AND CONVENTION CENTRE BALIGE - Fitri Yana; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the implementation of the duties of a sous chef in the food and beverage department at the Labersa Toba Hotel and Convention Centre Balige. Sous chef plays a major role in operational responsibility in the kitchen, especially in food processing, which is one of the income of most hotels. Professional food processing cannot be separated from the ability and expertise of a cook. In a large kitchen there are several staff who are responsible for several parts. The sous chef in the kitchen has carried out his duties competently in terms of planning, actuating and controlling. This study uses qualitative research methods and obtain data, the authors use interview, observation and documentation techniques. From the results of the research that the aouthors conducted 4 months, it was found that the implementation of the sous chef duties at the Labersa Toba Hotel and Convention Centre Balige had gone well according to standard operating procedures. But naturally there must be obstacles faced by the sous chef during the implementation of the task. Keyword : Task Implementation, Sous Chef, Kitchen